2021
DOI: 10.1016/j.conctc.2021.100742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuromuscular electrical stimulation therapy on physical function in patients with COVID-19 associated pneumonia: Study protocol of a randomized controlled trial

Abstract: Purpose Neuromuscular electrical stimulation (NMES) has been considered as a promising approach for the early rehabilitation of patients during and/or after intensive care unit (ICU) stay. The overall objective of this study is to evaluate the NMES effectiveness to counteract the post-ICU impairment in physical function of COVID-19 patients. The specific aim of this manuscript is to describe the study design, protocol, content of interventions, primary and secondary outcomes and to discuss the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, a meta‐analysis of 10 RCTs has reported that post‐ICU physical rehabilitation may not necessarily improve health and mental quality of life at 6‐ to 12‐month 136 . Nonetheless, more RCTs are ongoing that sought to test other potential non‐pharmaceutical therapies (e.g., neuromuscular electrical stimulation, virtual reality and rehabilitation programs) for post‐ICU survivors of COVID‐19 137–141 …”
Section: Resultsmentioning
confidence: 99%
“…However, a meta‐analysis of 10 RCTs has reported that post‐ICU physical rehabilitation may not necessarily improve health and mental quality of life at 6‐ to 12‐month 136 . Nonetheless, more RCTs are ongoing that sought to test other potential non‐pharmaceutical therapies (e.g., neuromuscular electrical stimulation, virtual reality and rehabilitation programs) for post‐ICU survivors of COVID‐19 137–141 …”
Section: Resultsmentioning
confidence: 99%
“…Today, this technology has been demonstrated to improve muscle strength in ICU COVID-19 patients ( 21 ). However, there is still a lack of randomized studies ( 22 ) to confirm its efficacy. Thus, it is unclear whether this adjunctive therapy prevents lower-extremity muscle deconditioning in ICU COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…In previous RCTs, NMES has shown to be a valuable, straightforward, and non-invasive adjunct therapy to pulmonary rehabilitation for COPD patients (Bourjeily-Habr et al, 2002). It has also been shown to improve physical and functional performance in patients with pneumonia (Minetto et al, 2021), and post-intensive care syndrome (Minetto et al, 2021). However, no conclusive recommendations have been provided to support NMES as a non-pharmacological intervention for patients with PCS.…”
Section: Discussionmentioning
confidence: 99%
“…To date, physical therapy is the standard care for patients with PCS, and no conclusive recommendations have been provided to support other nonpharmacological interventions for this condition. In addition, it has been hypothesized that Neuromuscular Electrical Stimulation (NMES) is a safe and effective non-pharmacological intervention for improving muscle weakness in different pulmonary diseases (Minetto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%